(untitled) (المجلة الدولية للبحوث العلمية, 2024)
Trona is one of the natural forms of sodium carbonate minerals, it is well known as (sesquicarbonate) or (trona) and is known in Arabic as (natron) or (atrun). The possibility of determining some constituents of trona ore was studied, using the methods of purification, separation, titration gravimetric analysis and calcination. The aim of this study is to determine the major chemical Constitutes of three types of trona from different locations in Sudan, A chemical analysis has been carried out on these samples to determine their major constituents, and their quantities, using different analytical techniques. From the results obtained, it was found that the percentage of carbonate and bicarbonate for Northen, Westen, and Southern Darfour, were (35.52%: 18.19%), (25.87%: 12.20%) and (16.82%: 6.24%) respectively. These results suggest that the use of trona deposits for soda ash production is promising and important. We can recommend the use of trona as a source for the production of sodium carbonate.